2019
DOI: 10.1016/j.celrep.2019.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Interstrand Crosslink Proximal Replisomes Is Dependent on ATR, FANCM, and FANCD2

Abstract: SUMMARY Eukaryotic replisomes are driven by the mini chromosome maintenance (MCM [M]) helicase complex, an offset ring locked around the template for leading strand synthesis by CDC45 (C) and GINS (G) proteins. Although the CDC45 MCM GINS (CMG) structure implies that interstrand crosslinks (ICLs) are absolute blocks to replisomes, recent studies indicate that cells can restart DNA synthesis on the side of the ICL distal to the initial encounter. Here, we report that restart requires ATR and is promoted by FANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 83 publications
(101 reference statements)
5
54
0
Order By: Relevance
“…These data demonstrated the association of DONSON with replisomes in cells with or without TMP/UVA treatment. Furthermore, they distinguished DONSON from FANCM, which, as shown previously, was not in complex with GINS proteins in either condition 29 .…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…These data demonstrated the association of DONSON with replisomes in cells with or without TMP/UVA treatment. Furthermore, they distinguished DONSON from FANCM, which, as shown previously, was not in complex with GINS proteins in either condition 29 .…”
Section: Resultssupporting
confidence: 76%
“…DONSON was also complexed with CDC45 and the GINS proteins indicating association with the helicase functional form of the replisome ( Supplementary Fig. 1f ), in contrast to replisomes bound by FANCM 29 . Proximity ligation assays (PLA) confirmed these interactions ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a mechanism involving traverse of an ICL by the replisome without significantly compromising fork progression has recently been described 56 . While the exact details of this process need to be elucidated, ICL traverse involves remodeling of the CDC45-MCM2-7-GINS (CMG) helicase 59 . It has been suggested that FANCM, BLM 60 , or an as yet unidentified helicase(s) facilitates replisome traverse in part by generating ssDNA beyond the ICL, which allows an open replicative helicase complex to re-encircle DNA after translocation 37 .…”
Section: Mcm8ip and The Regulation Of Replication Fork Progression Anmentioning
confidence: 99%
“…Prior to this, the MCM-complex may be able to perform its helicase function in the absence of GINS. Human dermal fibroblasts lacking GINS2 are also able to undergo mitosis, albeit at a slower rate, providing evidence that GINS-independent proliferation can also occur in mammalian cells (Barkley et al, 2009), and recent results suggest that other proteins, such as Fancm could substitute for GINS function under specific circumstances (Huang et al, 2019). It will be important to elucidate the identity of factors that can perform GINSlike function in young zebrafish embryos as they might be important, yet unrecognized, conditional components of the vertebrate replisome.…”
mentioning
confidence: 97%